System-on-a-Chip (SoC)-Based Hardware Acceleration for an Online Sequential Extreme Learning Machine (OS-ELM) - Safaei, A. (IEEE Xplore, 2020)
Machine learning algorithms such as those for object classiﬁcation in images, video content analysis, and human action recognition are used to extract meaningful information from data recorded by image sensors and cameras. Among the existing machine learning algorithms for such purposes, extreme learning machines (ELMs) and online sequential ELMs (OS-ELMs) are well known for their computational efﬁciency and performance when processing large datasets. The latter approach was derived from the ELM approach and optimized for real-time application. However, OS-ELM classiﬁers are computationally demanding, and the existing state-of-the-art computing platforms are not efﬁcient enough for embedded systems, especially for applications with strict requirements in terms of low power consumption, high throughput, and low latency. This paper presents the implementation of an ELM/OS-ELM in a customized system-on-a-chip ﬁeld-programmable gate array-based architecture to ensure efﬁcient hardware acceleration. The acceleration process comprises parallel extraction, deep pipelining, and efﬁcient shared memory communication.